2011
DOI: 10.1002/anie.201102022
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Linkage Isomerism in [Ni(Et4dien)(NO2)2]: A Combined Thermal and Photocrystallographic Structural Investigation of a Nitro/Nitrito Interconversion

Abstract: Photocrystallography is a rapidly developing technique that enables the full three-dimensional structure of a molecule in a metastable or excited state to be elucidated when a single crystal of the complex is photoactivated by visible or UV light.[1] Pioneering work in the areas of both molecular and macromolecular photocrystallography has allowed the crystallographic characterization of species with microsecond and sub-microsecond lifetimes. [2, 3] Of equal importance are the detailed studies on the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 30 publications
2
62
1
Order By: Relevance
“…2 and the data, returning an estimation of EA = -1.6 (± 0.05) kJ mol -1 . This value is smaller than that obtained for [Ni(Et4dien)(NO2)2], 14 but is still comparable. The values for ΔH, ΔS and EA are indicative of a low energy barrier between the isomers, suggesting they are close in energy.…”
Section: (A) (B)contrasting
confidence: 66%
“…2 and the data, returning an estimation of EA = -1.6 (± 0.05) kJ mol -1 . This value is smaller than that obtained for [Ni(Et4dien)(NO2)2], 14 but is still comparable. The values for ΔH, ΔS and EA are indicative of a low energy barrier between the isomers, suggesting they are close in energy.…”
Section: (A) (B)contrasting
confidence: 66%
“…24 This is in contrast to the majority of photo-switchable nitrite linkage isomers reported, which more typically show an expansion of the crystal on activation. [6][7][8] The unit cell reduction is anisotropic: while the b and c axes contract by −0.1256IJ5) Å and −0.230IJ1) Å respectively, the a-axis lengthens by 0.0867(5) Å. Given that the 1-D chains of metal cations extend parallel to the a-axis, it might be argued that the expansion in this direction is a direct result of the isomerisation.…”
Section: Complex 1: Steady-state Photocrystallographymentioning
confidence: 99%
“…1 Photo-switching between linkage isomers can be achieved in both solution and the solid-state, with irradiation of the solid leading to the production of a metastable state (MS) isomer below some critical temperature. 2 In situ photocrystallographic studies have to-date revealed the structures of various MS linkage isomers, including nitrosyl, 3,4 nitrite, [5][6][7][8] sulfur dioxide, [9][10][11] and di-nitrogen 12 systems.…”
Section: Introductionmentioning
confidence: 99%
“…[4] More recently, we have also reported interesting thermal and photo-isomerisation behaviour in the complex [Ni(Et4dien)(NO2)2], (Et4dien = N,N,N',N'-tetraethyldiethylenetriamine). [5] Steady-state photocrystallographic studies with this system will be discussed. Excitation with 500 nm LED light produces a metastable endonitrito isomer at low temperature (100 K), with 100 % photo-conversion in the single crystal.…”
mentioning
confidence: 99%